REKONSTRUKSI TEORI KEPEMIMPINAN PENDIDIKAN: MEMBANGUN KERANGKA HOLISTIK BAGI SEKOLAH ABAD KE-21 [RECONSTRUCTING EDUCATIONAL LEADERSHIP THEORY: BUILDING A HOLISTIC FRAMEWORK FOR 21ST CENTURY SCHOOLS] - Putu Ayu Novita; Yohana F. Cahya Palupi Meilani (Universitas Pelita Harapan, 2025)
21st century education faces complex challenges due to technological disruption, social change, and demands to improve the quality of learning. Unfortunately, many educational institutions still apply a partial and less adaptive approach to leadership. This research aims to build a holistic leadership framework that is more integrative and contextual. A PRISMA-based meta-analysis method was used to review 150 Scopus Q1–Q2 (2018–2024) articles, with a final selection of the 10 most relevant articles. The results of the analysis show that a combination of transformational, instructional, digital, and distributed leadership can increase learning effectiveness, teacher participation, management efficiency, and institutional adaptability. The proposed Holistic Leadership Framework model combines transformational vision, academic focus, technology utilization, and organizational collaboration. A key contribution of this study is the integration of various leadership approaches into a single strategic framework that is applicable to principals and policymakers. The study also encourages further validation in different contexts to test the effectiveness of its implementation. Abstrak Bahasd Indonesia: Pendidikan abad ke-21 menghadapi tantangan kompleks akibat disrupsi teknologi, perubahan sosial, dan tuntutan peningkatan mutu pembelajaran. Sayangnya, banyak institusi pendidikan masih menerapkan pendekatan kepemimpinan yang parsial dan kurang adaptif. Penelitian ini bertujuan membangun kerangka kepemimpinan holistik yang lebih integratif dan kontekstual. Metode meta-analisis berbasis PRISMA digunakan untuk mereview 150 artikel Scopus Q1–Q2 (2018–2024), dengan seleksi akhir 10 artikel paling relevan. Hasil analisis menunjukkan bahwa kombinasi kepemimpinan transformasional, instruksional, digital, dan terdistribusi mampu meningkatkan efektivitas pembelajaran, partisipasi guru, efisiensi manajemen, serta daya adaptasi institusi. Model Holistic Leadership Framework yang diusulkan menggabungkan visi transformasional, fokus akademik, pemanfaatan teknologi, dan kolaborasi organisasi. Kontribusi utama studi ini adalah integrasi berbagai pendekatan kepemimpinan ke dalam satu kerangka strategis yang aplikatif bagi kepala sekolah dan pembuat kebijakan. Penelitian ini juga mendorong validasi lanjutan dalam konteks yang berbeda untuk menguji efektivitas implementasinya.